Practices of food producers in producing halal food products in Malaysia - Mat Issa @ Zakaria, Zuraini; Hamdan, Haslenna; Wan Muda, Wan Rohanizan; Jusoff, Kamaruzaman (Institute of Interdisciplinary Business Research, 2009)
Malaysian Government has taken proactive steps in making Malaysia as a regional halal hub. Tremendous potential in the development and production of halal products especially food should be expected. The aim of this study is therefore to investigate the level of practice by the food producers in producing halal food products. Studied variables are adherence on halal labeling, understanding on halal process and procedures and awareness on halal demand, and associated factor including food producers’ practices. A set of questionnaires was designed and sent to 60 selected food producers in Malaysia by post. The data collected were then analyzed using the SPSS version 13 for descriptive statistics, Pearson Correlation Coefficient, and also multiple regressions. The results showed that most of the respondents, who are Muslim food producers, claimed that they have obtained halal certification from JAKIM. The results also revealed that all the adherence towards halal labeling, understand the halal processes and procedures, and aware of consumers’ demand towards halal food have significantly related to the halal practices and were moderately positively correlated. This present study can be used to serve as a basis for future research in determining the level of halal practices by all food producers in Malaysia.